Atmosphere-sensitive photoluminescence of CoxFe3−xO4 metal oxide nanoparticles. Issue 54 (18th October 2021) - Klein, Julian; Kampermann, Laura; Saddeler, Sascha; Korte, Jannik; Kowollik, Oliver; Smola, Tim; Schulz, Stephan; Bacher, Gerd
Abstract : Co x Fe3− x O4 (0.4 < x < 2.5) nanoparticles show a broad green emission induced by surface OH-groups with a lower stability regarding UV-photoinduced dehydroxylation on Fe-rich ( x ≤ 1.6) nanoparticles. Abstract : In this work the photoluminescence (PL) of Co x Fe3− x O4 spinel oxide nanoparticles under pulsed UV laser irradiation ( λ exc = 270 nm) is investigated for varying Co/Fe ratios ( x = 0.4⋯ 2.5). A broad emission in the green spectral range is observed, exhibiting two maxima at around 506 nm, which is dominant for Fe-rich nanoparticles ( x = 0.4, 0.9), and at around 530 nm, that is more pronounced for Co-rich nanoparticles ( x > 1.6). As examinations in different atmospheres show that the observed emission reacts sensitively to the presence of water, it is proposed that the emission is mainly caused by OH groups with terminal or bridging metal–O bonds on the Co x Fe3− x O4 surface. Raman spectroscopy supports that the emission maximum at 506 nm corresponds to terminal OH groups bound to metal cations on tetrahedral sites ( i.e., Fe 3+ ), while the maximum around 530 nm corresponds to terminal OH groups bound to metal cations on octahedral sites ( i.e., Co 3+ ). Photoinduced dehydroxylation shows that OH groups can be removed on Fe-rich nanoparticles more easily, leading to a conversion process and the formation of new OH groups with different bonds to the surface. As such behavior is not observed for Co x Fe3− x O4 with x > 1.6, we conclude that the OH groups are more stable against dehydroxylation on Co-rich nanoparticles. The higher OH stability is expected to lead to a higher catalytic activity of Co-rich cobalt ferrites in the electrochemical generation of oxygen.